2009
DOI: 10.2495/cmem090121
|View full text |Cite
|
Sign up to set email alerts
|

Study of the thermo-physical properties of bitumen in hydrocarbon condensates

Abstract: The reduction of viscosity with inappropriate diluents could lead to asphaltene precipitation. To use condensates effectively however, their effects on asphaltene precipitation and deposition must be well examined. In this study, the influence of inter-particle interactions of asphaltene on the viscosity and heat of mixing in solutions of bitumen-condensate mixtures are compared to those of bitumen in aromatic solvents and in condensate-toluene mixtures. Three bitumen, two heavy oils, and five condensates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…As expected, the results clearly show that the presence of asphaltenes, even in a small amount, in crude oil has a significant impact on the viscosity of the oil. The results are consistent with those obtained in our previous work with calorimetric method [8]. Viscosity-temperature relationship for Warri light crude oil with different wt% Plover Lake bitumen.…”
Section: Discussion Of Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As expected, the results clearly show that the presence of asphaltenes, even in a small amount, in crude oil has a significant impact on the viscosity of the oil. The results are consistent with those obtained in our previous work with calorimetric method [8]. Viscosity-temperature relationship for Warri light crude oil with different wt% Plover Lake bitumen.…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…The mixture was agitated using a G10 gyrotary shaker for 24 hours, left to stand for two hours and filtered using a 7.0cm whatman filter paper as described in ASTM 863-63. The procedure used to recover the deasphalted bitumen has been documented in our previous publication [8]. To prepare the mixtures of light crude oil containing 5wt% to 40wt% bitumen, a known amount of the bitumen was added quantitatively to the light crude oil in increment of 5wt%.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The diameter of the throttle holes of the separator corresponds to the value d 0 =3,5×10 4 m. The relative calculation error was 13%. The deviation of the theoretical curve from the experimental values for the last rows of the throttle holes is explained by the limitation of the model's application area for the initial stage of hydrodynamic cavitation, when Re=(1,5-10,0)×10 4 . The proposed stochastic model does not take into account such consequences of the evolution of cavitation bubbles as possible splicing of bubbles, growth of their size, collapse, etc.…”
Section: Resultsmentioning
confidence: 87%
“…Comparison of theoretical results according to expression (12) and experimental data obtained on a pilot plant by Lebedev et al 28 is shown in Figure 2. The analysis was performed with the degree of valve opening ζ=0,6, when the values of the model parameters are equal to: E 0 = 1,97×10 -8 J; M = 2,01×10 -12 kg×m 2 /c; Re y =9,8×10 4 . The diameter of the throttle holes of the separator corresponds to the value d 0 =3,5×10 4 m. The relative calculation error was 13%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation